2001
DOI: 10.1210/endo.142.8.8299
|View full text |Cite
|
Sign up to set email alerts
|

Prepro-Orexin and Orexin Receptor mRNAs Are Differentially Expressed in Peripheral Tissues of Male and Female Rats

Abstract: Orexins are produced specifically by neurons located in the lateral hypothalamus. Recent results suggested peripheral actions of orexins. Therefore, we analyzed the mRNA expression of prepro-orexin and the orexin receptor subtypes OX(1) and OX(2) in peripheral rat tissues. Using real-time quantitative RT-PCR we detected significant amounts of prepro-orexin mRNA in testis, but not in ovaries. OX(1) receptor mRNA was highly expressed in the brain and at lower levels in the pituitary gland. Only small amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
149
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(159 citation statements)
references
References 34 publications
8
149
2
Order By: Relevance
“…The expression of orexin receptors in the pituitary is also determined by gender, which once again emphasizes the importance of the animals' hormonal status. The expression of the OX1R gene was higher in the pituitary of male rats than in female rats (Jöhren et al, 2001).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The expression of orexin receptors in the pituitary is also determined by gender, which once again emphasizes the importance of the animals' hormonal status. The expression of the OX1R gene was higher in the pituitary of male rats than in female rats (Jöhren et al, 2001).…”
Section: Introductionmentioning
confidence: 81%
“…The expression of orexin receptors in the pituitary is also determined by gender, which once again emphasizes the importance of the animals' hormonal status. The expression of the OX1R gene was higher in the pituitary of male rats than in female rats (Jöhren et al, 2001).Research advances over the past decade have confirmed that the orexin system participates in the control of rat and human pituitary. In the existing body of research, there are no studies investigating the presence of orexins in the porcine pituitary and possible impact of hormonal status of the animals connected with the phase of the estrous cycle on orexin concentrations.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Although OX expression in the brain is only located in the LHA-perifornical area (Broberger et al 1998a;Elias et al 1998b;Horvath et al 1999), OX receptors show a widespread distribution in the CNS, with high levels of abundance in some hypothalamic nuclei (ARC, DMH, LHA, PVH and VMH; Marcus et al 2001;Backberg et al 2002). OX receptors are also present in the adrenal gland (López et al 1999), pituitary (Blanco et al 2001 gut (Kirchgessner & Liu, 1999), testis, kidney, ovary and placenta (Johren et al 2001).…”
Section: Hypothalamic Neuropeptides Regulating Food Intakementioning
confidence: 99%
“…The presence of oxA has been detected in the human placenta which is, however, a transient structure related only to pregnancy (Nakabayashi et al, 2003). Both orexin receptors are expressed in rat ovaries and fluctuate during the estrous cycle (Jöhren et al, 2001;Silveyra et al, 2007). The expression of prepro-orexin and of an orexin receptor sharing close similarities with ox2R has been described in the ovary of a non-mammalian species, the chicken (Ohkubo et al, 2003).…”
mentioning
confidence: 99%